2008
DOI: 10.1111/j.1524-4733.2007.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes and Health-Care Resource Utilization in Patients with Psoriasis Treated with Etanercept: Continuous versus Interrupted Treatment

Abstract: Continuous etanercept treatment provided greater sustained improvements in PROs than interrupted therapy; however, interrupting etanercept therapy, if needed, has predictable and manageable effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 21 publications
5
42
0
Order By: Relevance
“…Secondly, this population gave us the ideal opportunity to explore the effect of TNF antagonism on 5-HTT. Earlier research in this population has shown that TNF antagonism was associated with an antidepressant effect that was independent of disease improvement (Gelfand et al, 2008;Krishnan et al, 2007;Langley et al, 2010;Tyring et al, 2006). Consistent with previous studies, TNF-α explained only around 3% of and brain stem 5-HTT availability explained only around 7% variance in depression severity (Gryglewski et al, 2014;Valkanova et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…Secondly, this population gave us the ideal opportunity to explore the effect of TNF antagonism on 5-HTT. Earlier research in this population has shown that TNF antagonism was associated with an antidepressant effect that was independent of disease improvement (Gelfand et al, 2008;Krishnan et al, 2007;Langley et al, 2010;Tyring et al, 2006). Consistent with previous studies, TNF-α explained only around 3% of and brain stem 5-HTT availability explained only around 7% variance in depression severity (Gryglewski et al, 2014;Valkanova et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…Etanercept reduced depression 29% in psoriasis patients with minimal depression [24]. Ustekinumab reduced depression 55%; 27% and 12% of patients reported depression before and after treatment, respectively [25].…”
Section: Impact Of Treating Psoriasis On Depressionmentioning
confidence: 95%
“…In a case series, etanercept monotherapy reduced depression as measured by the Hamilton Depression Rating Scale, but not according to the Beck Depression Inventory-II [40]. In the context of comorbid psoriasis and depression, etanercept reduced depression by 29% as measured by the Beck Depression Inventory, while adalimumab reduced depression by 18.5% as measured by the Zung Self-Rating Depression Scale [41,42]. These results suggest that depression is reduced by anti-TNF-a biologics; however, the variability in depression screening tools hinders comparison between different medications in this treatment class (Table 1).…”
Section: Biologic Use In Psoriasis: Effects On Depressionmentioning
confidence: 99%